Fatores responsáveis pela mudança no desempenho da indústria das análises clínicas no Brasil - Pereira, Flavia Malta Fernandes (2012)
The clinical laboratories are constantly exposed to changes that may be caused by several factors, whether economic or not. Today clinical laboratories face several challenges, such as the pressure to reducing costs and improving service quality while facing the need of attaining ever higher levels of automation and technical quality. Being aware of such challenges and reacting to them in sufficient timing so as to assure their business survival is the main challenge of laboratories' managers, who are better prepared technically than managerially. The urgent need for a new strategy in this aerea is a reality This study aims to survey the factors that were responsible for the change in performance in Brazilian laboratories. We raised three important factors defined by type of portfolio, automation with LIS system and outsourcing, which were presented by 15 non-financial indicators. We developed a structural equation model with which we assessed the significance and magnitude of each of these factors on laboratory performance. We found that only one of such factors showed significance, which was the automation with LIS system. Thus, our research shows that this factor is the main agent of change in performance in clinical laboratories in Brazil.